TRANSATLANTIC TRADE AND INVESTMENT PARTNERSHIP (TTIP): THE POSSIBLE IMPACT ON THE EUROPEAN UNION AND NORTH AMERICA - Wassenberg, Nicole (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
The Transatlantic Trade and Investment Partnership (TTIP) is projected high-standard and inclusive free trade agreement which is being conversed between the United States (US) and European Union (EU). Transatlantic Trade and Investment Partnership is a chain of trade negotiations operating between EU and US. The TTIP is mainly about decreasing the regulatory obstacles to trade to open up a way for bigger businesses such as environmental legislation, food safety, sovereign powers of the individual nations and also banking regulations. The US and EU are two of the most integrated countries when it comes to economy globally. It is as a result of their trade in services, investments and the high commercial presence in each other's financial prudence. These two regions support each other when it comes to the economy, and that's why they are good trading partners in products and services. The EU and U.S trade and investment partnership which is sometimes referred to as transatlantic economy has a significant global relationship and creates a mutually beneficial understanding between the two states (Hoekman and Kostecki, 2009). The TTIP is one of the largest trade and investment partnership in the world and also the most significant because of its absolute size. It has many for example the European Union has 28 member states which include: Bulgaria, Cyprus, Belgium, Austria, Czech Republic, Estonia, Germany, Denmark, Finland. Greece, Ireland, Hungary, Italy, Netherlands, Poland, Slovenia, Lithuania, Romania, Spain, Latvia, Sweden, Portugal and United Kingdom are also part of the partnership. The initial negotiations on TTIP which was to become the first largest bilateral free trade and investment partnership agreement were earlier supported by a paramount and independent study of the Center for Economic Policy Research (CEPR). The study by CEPR was called Reduction of the Transatlantic Barriers to Trade and investment. The negotiations were mainly to provide independent advice to the two negotiators based on the additional research. Despite, TTIP being one of the largest trade and investment partnership, it has created both negative and positive impacts on the two states. There are benefits t being enjoyed by the member states such as job creation and home growth. The EU depends on the US exports; they can get investments from the US and also import the goods and services they require (Khanna, Palepu, and Sinha, 2005). Other positive impacts of the TTIP includes; upholding and promoting human rights, governing in a transparent manner that can hold to account individuals in authority and also has markets that can be open to free and reasonable competition and is well-regulated market areas. TTIP also protects the people and the planet through their international rules. For example, the rules look at everyone's health, their condition at workplaces, the endangered species around them and the entire environment. There are also challenges that have come out from TTIP in the field of politics and economics, poor labor standards, workers' rights and security of their workplaces, democracy, and state authority. Foreign shareholder protection, public health and the environment as a whole, health care, consumer safety and food security, climate change and environment protection, banking regulation and privacy and many others. Some competitors challenge the TTIP on slowness in services than in goods leading to difficulty in opening markets in service areas.